2006
DOI: 10.1086/501489
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-ResistantStaphylococcus aureusControl: We Didn't Start the Fire, but It's Time to Put It Out

Abstract: The prevalence of healthcare-associated infections (HAIs) caused by multidrug-resistant organisms has significantly increased over the past decade, according to the measurements of the Centers for Disease Control and Prevention, and will likely continue to climb. 1 ' 2 Currently, more than 70% of HAIs are caused by bacteria that are resistant to at least 1 of the drugs most commonly used to treat these infections. 3 These HAIs have been associated with increased cost and mortality, compared with infections due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…aureus colonization and the most frequently screened and recommended site for specimen collection due to the satisfactory sensitivities of tests with that type of specimen and the ease with the specimen may be obtained (15,18,20), other recent studies have shown that sampling of other body sites (the oropharynx, perianal region, and groin) may enhance the sensitivity of screening for MRSA and predict the likelihood of S. aureus infection (3,7,11,14,22). Most importantly, it is agreed that the culture of specimens from more body sites would yield higher rates of recovery, but the increased resources required for the screening of specimens from multiple sites outweigh the incremental increase in yield that would be attained (5).…”
Section: And Mannitol Salt Agar [Msa]) a Multicenter Study (Includinmentioning
confidence: 99%
See 1 more Smart Citation
“…aureus colonization and the most frequently screened and recommended site for specimen collection due to the satisfactory sensitivities of tests with that type of specimen and the ease with the specimen may be obtained (15,18,20), other recent studies have shown that sampling of other body sites (the oropharynx, perianal region, and groin) may enhance the sensitivity of screening for MRSA and predict the likelihood of S. aureus infection (3,7,11,14,22). Most importantly, it is agreed that the culture of specimens from more body sites would yield higher rates of recovery, but the increased resources required for the screening of specimens from multiple sites outweigh the incremental increase in yield that would be attained (5).…”
Section: And Mannitol Salt Agar [Msa]) a Multicenter Study (Includinmentioning
confidence: 99%
“…Recent reports by Salgado and Farr (17) and Lucet et al (13) have shown that the organisms in positive cultures of clinical specimens routinely submitted from patients represent only a small fraction of the reservoir of antibiotic-resistant pathogens, and the largest source for nosocomial spread was attributed to asymptomatic, colonized patients who went unrecognized and unisolated in the absence of ASCs. Additionally, consensus suggests that a restricted formulary alone is unlikely to prevent the emergence and persistence of MRSA and that the use of contact precautions is important to prevent the spread of MRSA from colonized patients (5).While the anterior nares are the most common site of S.aureus colonization and the most frequently screened and recommended site for specimen collection due to the satisfactory sensitivities of tests with that type of specimen and the ease with the specimen may be obtained (15,18,20), other recent studies have shown that sampling of other body sites (the oropharynx, perianal region, and groin) may enhance the sensitivity of screening for MRSA and predict the likelihood of S. aureus infection (3,7,11,14,22). Most importantly, it is agreed that the culture of specimens from more body sites would yield higher rates of recovery, but the increased resources required for the screening of specimens from multiple sites outweigh the incremental increase in yield that would be attained (5).…”
mentioning
confidence: 99%
“…36 When testing only clinical isolates, up to 85% of MRSA cases are undetected. 30,33,37 At least 25e50% of MRSA cases are undetected when screening only the nose. 30,31,34,37 The combination of throat and perineum may have the highest detection rate (98.3%).…”
Section: Discussionmentioning
confidence: 99%
“…30,33,37 At least 25e50% of MRSA cases are undetected when screening only the nose. 30,31,34,37 The combination of throat and perineum may have the highest detection rate (98.3%). 24 Outbreaks may be extended by lack of testing of the throat.…”
Section: Discussionmentioning
confidence: 99%
“…The movement for MRSA control is timely and necessary [188,[223][224][225][226][227][228]: at all levels, we need more Mutos and Farrs and Dancers and Simmons and Casewells and Vos and Verbrughs and Farringtons and their like-minded. Institutions with high endemicity can achieve control [227].…”
Section: Moving Forward On Strengthmentioning
confidence: 99%